The meanings of work : essay on the affirmation and negation of work - Antunes, Ricardo, 1953- (Historical materialism book series ;, 2012)
Contrary to the affirmation of the end of labour, The Meanings of Work explore the complexity of the working class today; the sexual division of labour and transversalities between the dimensions of class and gender; globalisation of capital and labour.